(untitled) (Al-Farooq Journal of Sciences, 2026)
At an important time for Libyan education reform, there are relatively few publications providing the evidence-based research for informed decision-making. As countries across the Arab world seek to improve their knowledge-based economies, Libya faces increasing pressure to expand its education research in order to support schools and universities in delivering quality provision. Existing literature shows that research output in developing and post-conflict contexts is often uneven, and in Libya, where education reform is a clear priority, there is still limited understanding of the scale and focus of research activity in this field. This study addresses that gap through a bibliometric analysis of education-related research associated with Libya, providing insight into the current evidence base and its alignment with national needs. This paper examines the evidence-based research supporting the national education provision in Libya. Analysis of Libya-related publications over a five-year period identified 551 outputs associated with education-related keywords. However, a large proportion of these were classified within biomedical and health-related fields. When education-specific categories (‘Education’ and ‘Education Systems’) were isolated, approximately 206 publications were identified. This indicates that, although education is visible as a research theme, it is not consistently developed as a distinct field. In addition, when considered within the parameters of overall publication volume in Libya, the overall volume of education-focused research remains modest. This is particularly concerning in the Libyan context as it has clear implications for evidence-based decision-making and the long-term development of the education system.